Solid waste management critical issues for developing countries - Thomas-Hope, Elizabeth M. (Canoe Press, University of the West Indies, 1998)
"This volume presents a collection of papers which, with perspectives from Africa and the Caribbean, raise critical issues in the management of solid waste. It is intended to offer a basis for discussion among the wide range of disciplines and sectors involved in solid waste management and suggest directions for future work in the theoretical and practical dimensions of the challenge with which developing countries are confronted"--Back cover.